2021
DOI: 10.1002/chem.202101948
|View full text |Cite
|
Sign up to set email alerts
|

How to Look for Compounds: Predictive Screening and in situ Studies in Na−Zn−Bi System

Abstract: Here, the combination of theoretical computations followed by rapid experimental screening and in situ diffraction studies is demonstrated as a powerful strategy for novel compounds discovery. When applied for the previously "empty" NaÀ ZnÀ Bi system, such an approach led to four novel phases. The compositional space of this system was rapidly screened via the hydride route method and the theoretically predicted NaZnBi (PbClF type, P4/nmm) and Na 11 Zn 2 Bi 5 (Na 11 Cd 2 Sb 5 type, P � 1) phases were successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Predictive synthesis remains an important goal for materials chemists. While many joint computational-experimental synthesis efforts have been reported in literature, trial-and-error approaches remain the dominant paradigm. Within this current paradigm, in situ X-ray diffraction (XRD) is a powerful technique for materials discovery. , Sometimes called “panoramic synthesis,” , in situ X-ray diffraction allows for observation of solid-state reactivity as it happens.…”
Section: Introductionmentioning
confidence: 99%
“…Predictive synthesis remains an important goal for materials chemists. While many joint computational-experimental synthesis efforts have been reported in literature, trial-and-error approaches remain the dominant paradigm. Within this current paradigm, in situ X-ray diffraction (XRD) is a powerful technique for materials discovery. , Sometimes called “panoramic synthesis,” , in situ X-ray diffraction allows for observation of solid-state reactivity as it happens.…”
Section: Introductionmentioning
confidence: 99%
“…Complex pnictides of d-metals have long been the focus of researcher's attention due to the diversity of their structures combined with interesting physical properties [1][2][3][4][5][6]. The discovery of superconductors based on layered ferroarsenides in 2008 caused great interest in the scientific community and stimulated the search for analogues of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The former turned out to be isostructural to the 111 Fe‐based superconductors, whereas the latter crystallizes in a different space group [18] . After some time, the compound NaZnBi was obtained independently, [19] and the authors [19] concluded that there was a certain zinc deficiency in its structure. It is interesting to note that the synthesis of compounds Na TM Bi ( TM =Zn, Cd) confirmed the theoretical prediction of their existence, although the observed crystal structure was found to be different [20–22] …”
Section: Introductionmentioning
confidence: 99%